2004
DOI: 10.1300/j018v27n01_11
|View full text |Cite
|
Sign up to set email alerts
|

Spaced-Retrieval with Probable Alzheimer's

Abstract: Four older adults with probable Alzheimer's disease (AD) were trained to recall everyday objects using the spaced-retrieval technique. Two persons who had participated in a previous spaced-retrieval training program were retested here to provide new evidence on the long-term effectiveness of the training. Two others who had not been tested previously served as controls. Spaced-retrieval training consisted of six-hour-long sessions given on alternate days over a two-week period. On each trial, participants sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…To our knowledge, our results are the first to show retention of an association that includes social information about the target person (i.e., name, face, and occupation). Our findings are also compatible with prior research in which spaced retrieval effects were found using common household objects as the training material (Cherry & Simmons-D'Gerolamo, 2004, 2005.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, our results are the first to show retention of an association that includes social information about the target person (i.e., name, face, and occupation). Our findings are also compatible with prior research in which spaced retrieval effects were found using common household objects as the training material (Cherry & Simmons-D'Gerolamo, 2004, 2005.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the latter, providing semantic cues to support encoding as well as retrieval has been found to produce similar memorial benefits for persons with AD and healthy older adults. 54,87,88 Because memory is enhanced when relevant information is presented at both the encoding and retrieval stages, not having the iPad available during the encoding stage in the present study may have had a negative effect on the participants' response outcomes. If instead we had introduced and drew attention to the iPad before and during the event, it may have supported encoding of the iPad as an integral part of the event.…”
Section: Cued Recallmentioning
confidence: 86%
“…Adjusting the spaced retrieval training, for example, by extending training intervals or training sessions, may lead to more durable representations of the core details. 54 Different SR training and interval schedules have been applied in previous SR studies. Additional training sessions may provide participants with more opportunities to encode the target core details to the point where their spontaneous recall performance would plateau, reaching a state of little or no change following a steep increase.…”
Section: Spontaneous Recallmentioning
confidence: 99%
See 1 more Smart Citation
“…If subsequent trials are successful, intervals are increased by approximately doubling each inter-trial interval (i.e., 5, 10, 20, 40, 60, 120 seconds, 4, 8, 16 minutes). If a recall attempt is unsuccessful, then the to-be-learned information is presented again, immediate recall solicited and the next inter-trial interval goes back to that of the previous successful attempt (see for example : Brush & Camp, 1998;Camp, 1998;Cherry & Simmons-D'Gerolamo, 2004;. Participants were trained to an achievement criterion of a 20-minute inter-trial interval.…”
Section: Interventionmentioning
confidence: 99%